COMPARATIVE PHARMACEUTICO-ANALYTICAL STUDY OF SARJIKA KSHARA PREPARED BY THREE DIFFERENT METHODS - Gupta Tarun; Zala Upendra.U.Zala; 3Umrethia B.L.; Kalsariya B.D. (International Journal of Applied Ayurved Research, 2019)
Chyavanprasha Avaleha is widely prescribed & even very popular as an over the counter product. There are various references for Chyavanprasha Avaleha in Ayurvedic texts. Among them, references in Charaka Samhita and Sharangadhara Samhita are significant. The rationality and utility of these techniques of preparation need to be evaluated. Till now studies done on Chyavanprasha Avaleha have not highlighted the differences between the two methods. Hence this study was undertaken, which was classified in to two divisions Pharmaceutical study, Analytical study prepared by two methods. Preparation of Chyavanprasha Avaleha as carried out as per references of Charaka Samhita and Sharangdhara Samhita. The method of preparation was same in both the references except in frying of Amalaki pulp where, Charaka Samhita mentioned both Ghrita & Taila, whereas Sharangdhara Samhita mentioned only Ghrita. Chyavanprasha Avaleha was subjected to analytical study to establish the standards in terms of Organoleptic Characters and Physicochemical constants, which were carried out at SDM Centre for research in Ayurveda & Allied sciences, Udupi. Results : Analysis of the results obtained from the Analytical study revealed that the total fat content was more in Chyavanprasha Avaleha prepared by Charaka Samhita method compared to Sharangdhara Samhita method.